BUSINESS POLICY AS RELATED TO ACCOUNTING. - Lay, Chester F. (The Accounting Review, 1929)
The article focuses on the effect of business policy upon accounting and vice-versa. The most pressing problem facing large enterprises is the problem of controlling the organization through co-ordination, so as to achieve teamwork in executing a united program. Natural growth, consolidations, development of chain systems, and other influences have increased the size, complexity, and territorial dispersion of individual concerns and have created a situation out of which methods of managerial control arise from necessity. The growth of knowledge as to "best" ways of business operation has thrown into the spotlight the tendency of individuals to follow their own inadequate methods. Gains from adopting methods of "best" practice, together with the value of consistency of action within the fields set by sound organization, is rapidly forcing the deliberate adoption of company and departmental policies to establish control over objectives and operating methods. Departmental policies are concerned with procedures instead of objectives, are determined systematically if not scientifically and are changeable to cope with changing conditions or the increasing knowledge of principles of business practice